EscapED: A Framework for Creating Educational Escape Rooms and Interactive Games to For Higher/Further Education. - Samantha Jane Clarke; Daryl J. Peel; Sylvester Arnab; Luca Morini; Helen Keegan; Oliver Wood (Serious Games Society, 2017)
Game-based learning (GBL) is often found to be technologically driven and more often than not, serious games for instance, are conceptualised and designed solely for digital platforms and state of the art technologies. To encourage a greater discussion on the potential benefits and challenges of a more holistic approach to developing GBL that promote human centered interactions and play for learning, the authors present the escapED programme. The escapED programme was conceived following the recent entertainment trend of escape rooms and is used for developing non-digital GBL approaches within education. escapED aids the design and creation of educational Escape Rooms and Interactive Gaming Experiences for staff and students in further/higher education settings. The paper first presents a pilot study that was used to assess the feasibility and acceptance of University teaching staff of embedding interactive GBL into a higher education environment. The authors then present the escapED theoretical framework that was used to create the prototype game for the pilot study as a tool to aid future design and development of on-site interactive experiences. The paper also presents an external developer report of using the escapED framework to develop a prototype game for teaching research methods to Southampton University students. Finally, the authors present a discussion on the use of the escapED framework so far and plans for future work and evaluation in order to provide engaging alternatives for learning and soft skills development amongst higher education staff andstudents.